Assessing EFL Textbooks for Indonesian High School Students - ., Sugiyanta; Said, Mashadi (Advances in Social Sciences Research Journal, 2018)
This study assesses the EFL textbooks used for Indonesian high school students. It is aimed at assessing whether the textbooks meet the criteria of a good EFL textbook. For this purpose, an approach to content or document analysis was employed. The data were collected from an EFL textbook “Pathway to English”. The assessment was based on eight dimensions of textbook criteria including layout and design, subject and content, objective, types of texts, language skills, activities and tasks, grammar and vocabulary, and teachers’ book. The results of the assessment showed that the textbook mostly meets the criteria of a good EFL textbook. However, some items in dimensions one, two, three, four, six, and seven were not fulfilled. Moreover, the teacher’s book was not provided. This implies that the EFL textbook may be used for high school students with some revisions. Keywords: assessment, EFL textbooks, good EFL textbook, textbooks for high school students